In-plane behaviour of rammed earth under cyclic loading: Experimental testing and finite element modelling. (15th October 2016) - Miccoli, Lorenzo; Drougkas, Anastasios; Müller, Urs
Highlights: Cyclic in-plane shear-compression tests of rammed earth walls were carried out. The experimental behaviour was idealised using the performance-based engineering criteria. Test results were modelled with a non-linear model able to describe the pseudo-dynamic behaviour. The micro-modelling approach reproduces the collapse mechanism under cyclic in-plane shear-compression. The micro-modelling approach simulates with satisfactory accuracy the hysteresis loops and the damage pattern. Abstract: The purpose of this paper is to numerically simulate the in-plane behaviour of rammed earth walls under cyclic shear-compression tests. The experimental testing allowed obtaining the maximum horizontal loads, the displacement capacity and the level of non-linear behaviour of the respective load-displacement relationships as well as the failure modes. The calibration of the numerical model (finite element method) was carried out based on the experimental results. Within this framework, a micro-modelling approach was considered. The behaviour of the rammed earth material was simulated using a total strain rotating crack model. A Mohr-Coulomb failure criterion was used to reproduce the behaviour of the interfaces between the layers. Although the numerical results achieved a satisfactory agreement with the experimental results a sensitivity analysis of the parameters involved was performed. The sensitivity analysis aimed at determining which parameters of the model have a significant impact in the model's results. As expected the sensitivity analysis pointed out that the sliding failure occurrence is mainly influenced by two parameters of the interface elements: the interface tensile strength f i t and the friction angle φ. Moreover the cohesion c and the layers thickness showed a limited effect on the shear behaviour. It should be noted that the results mentioned above are related to the cases where a significant level of vertical compressive stress σ is employed.